PERANCANGAN APLIKASI PENGAJUAN PENERIMA BANTUAN KESEJATERAAN SOSIAL BERBASIS WEB PADA DINAS SOSIAL KOTA METRO - Siregar, Gunayanti Kemalasari; Widodo, Suyud (Jurnal Ilmiah Sistem Informasi (JISI), 2023)
The Social Service is a government institution that is given the mandate to regulate community welfare in accordance with Law no. 11 of 2009 concerning Social Welfare. The field of filing beneficiaries is one of the problems handled by the Social Service. Types of community assistance include Staple Food, Family Hope Program (PKH), Direct Cash Assistance (BLT) with certain conditions. With the number of beneficiaries currently totaling 9,205 Family Cards, processing of data on receiving assistance still utilizes data processing using Microsoft Excel. Where data processing using Microsoft Excel has drawbacks, including application users who must really understand the function, formula or logic, then if the user enters the formula incorrectly, the resulting data will be affected, besides that there will be many documents produced that are less stable for each version and for files with the latest version of Microsoft Excel requires a computer with medium to high specifications. Based on these problems, a special data processing application is needed for data on recipients of web-based social welfare assistance. The application aims to facilitate the work of service staff in the social welfare submission section in preparing recapitulation reports and reports on the list of people who will receive assistance at the Metro City Social Service.